2011
DOI: 10.1111/j.1574-6968.2011.02468.x
|View full text |Cite
|
Sign up to set email alerts
|

McsA and the roles of metal-binding motif in Staphylococcus aureus

Abstract: McsA is a key modulator of stress response in Staphylococcus aureus that contains four CXXC potential metal binding motifs at the N-terminal. S. aureus ctsR operon encodes ctsR, clpC and putative mcsA and mcsB genes. The expression of the ctsR operon in S. aureus was shown to be induced in response to various types of heavy metals such as copper and cadmium. McsA was cloned and overexpressed, and purified product was tested for metal binding activity. The protein bound to Cu(II), Zn(II), Co(II) and Cd(II). No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…MsrA2 reduces the S isomer of methionine sulfoxide, and MsrB reduces the R form, providing protection against oxidative stress [19]. In contrast, expression of ClpL, a protein involved in thermotolerance, was up-regulated in the sav1322 mutant strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MsrA2 reduces the S isomer of methionine sulfoxide, and MsrB reduces the R form, providing protection against oxidative stress [19]. In contrast, expression of ClpL, a protein involved in thermotolerance, was up-regulated in the sav1322 mutant strain.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, markedly lower expression levels of proteins involved in the stress response were observed in the sav1322 mutant, including the general stress protein 20U (Dps), methionine sulfoxide reductase A (MsrA2), and methionine sulfoxide reductase B (MsrB). MsrA2 reduces the S isomer of methionine sulfoxide, and MsrB reduces the R form, providing protection against oxidative stress [ 19 ]. In contrast, expression of ClpL, a protein involved in thermotolerance, was up-regulated in the sav1322 mutant strain.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of homology to adaptors identified in Bacillus subtilis, there are at least three adaptors in S. aureus, namely, McsB (SA0482), YjbH (SA0860), and TrfA (SA0857). Studies have indicated the involvement of each in various stress responses (27)(28)(29), but many gaps remain in our understanding of the various roles played by these adaptors in S. aureus. Details of the protein targets of these S. aureus adaptors are limited, and to date, only two target proteins have been described to be regulated by S. aureus adaptors.…”
mentioning
confidence: 99%
“…The ClpC subunit is required for growth at high temperatures (probably, it functions as a chaperone during heat shock) and for biofilm formation. It may act as a chaperone regulating CtsR activity [ 64 ] and participate in stress response to cadmium and copper ions [ 65 ]. In At.…”
Section: Resultsmentioning
confidence: 99%